Higher positive identification of malignant CSF cells using the cytocentrifuge than the Suta chamber - Sérgio Monteiro de Almeida; Indianara Rotta; Arnaldo José de Conto; Dario Antonelli Filho; Carlos Dabdoub Roda; Edna Yoshiko Yamada; Gisele M. B. Singer (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To define how to best handle cerebrospinal fluid (CSF) specimens to obtain the highest positivity rate for the diagnosis of malignancy, comparing two different methods of cell concentration, sedimentation and cytocentrifugation. Methods A retrospective analysis of 411 CSF reports. Results This is a descriptive comparative study. The positive identification of malignant CSF cells was higher using the centrifuge than that using the Suta chamber (27.8% vs. 19.0%, respectively; p = 0.038). Centrifuge positively identified higher numbers of malignant cells in samples with a normal concentration of white blood cells (WBCs) (< 5 cells/mm3) and with more than 200 cells/mm3, although this was not statistically significant. There was no lymphocyte loss using either method. Conclusions Cytocentrifugation positively identified a greater number of malignant cells in the CSF than cytosedimentation with the Suta chamber. However, there was no difference between the methods when the WBC counts were within the normal range.